The legacy of the UN Special Adviser on Solutions to Internal Displacement: How to maintain political momentum after the mandate expires - Nadine Knapp; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2024)
In June 2022, the Secretary-General of the United Nations (UN) published the "Action Agenda on Internal Displacement". It aims to fundamentally reform the way internal displacement is addressed. On the one hand, the focus must shift from short-term humanitarian aid to more development-oriented approaches. On the other hand, the governments directly affected must be more actively involved in the search for durable solutions. A UN Special Adviser, Robert Piper, has been entrusted with the implementation of the Action Agenda. Over the past two years, he has initiated positive developments in a number of countries and contributed to better coordination between relevant UN organisations. Beyond the mandate of the Special Adviser, which expires at the end of 2024, the progress he has achieved thus far must be secured. To this end, Germany should advocate for sustainable governance structures and campaign for internal displacement to be systematically taken into account in development and climate financing.
Keywords: 320; Secretary-General of the United Nations (UN); UN Special Adviser; Robert Piper; "Action Agenda on Internal Displacement"; internally displaced persons (IDPs); International Organization for Migration (IOM); United Nations High Commissioner for Refugees (UNHCR); United Nations Development Program (UNDP); Steering Group for Solutions to Internal Displacement; International Organization for Migration (IOM); UN Resident Coordinators (RCs)